The arts in individual transformation: Examples from the recycling social movement in São Paulo, Brazil - de Oliveira Jayme, Bruno; Heringer, Rebeca (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
How does individual transformation unfold within social movement learning (SML), a territory that mainly embodies learning as a collective practice? What are the roles of visual arts in mediating such transformation? We answer these questions by exploring discourses that emerged during visual arts workshops facilitated with members of the recycling social movement in São Paulo, Brazil. To do so, we intertwine arts-based research, SML, and transformative learning theories informed by Vygotskian’s cognitive development approach as an analytical tool. Findings suggest that during the art-making process, recyclers construct their visual thought, which enables their empowerment and agency as fundamental mediators of individual transformation.